The Role Of The Principal In Improving The Impelementation Of School-Based Management At MAN 1 Sungai Penuh: Quality Improvement And Enhancement - Putra, Eka (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The role of the school principal in improving the implementation of school-based management is very important because the principal brings direction leadership which can determine the success of implementing school-based management, because schools have such broad authority that the presence of a leader becomes very important. The purpose of this study is to deepen the role of school principals in implementing school-based management and what improvements and improvements to the quality of school-based management look like. This research uses a qualitative approach in a descriptive form. The results of this study are that the role of school principals in improving the application of school-based management is through the application of participatory management, namely improving the quality and service of education so that MAN 1 Sungai Full can compete and produce quality graduates both academically and non-academically. School-based management will work well if school members have initiative in carrying out their work and each individual's initiative needs to be valued.